Severe uterine haemorrhage requiring a blood transfusion in a dog with ovarian remnant syndrome and secondary pyometra. Issue 3 (26th May 2021) - Burchette, Hannah M.; Moyle, Rachel B.
Abstract: An 18‐month‐old female German Shepherd dog, previously reported to be spayed, presented to a referral clinic with a history of progressive haemorrhagic vulvar discharge resulting in clinical anaemia. An abdominal ultrasound showed an enlarged uterus and a retained right ovary; vaginoscopy revealed no obvious haemorrhage from the vagina or cervix, so the dog underwent exploratory laparotomy for ovariectomy and hysterectomy. Prior to surgery, the dog received a 15 ml/kg packed red blood cell transfusion and post‐operatively was given fresh frozen plasma due to significant blood loss into the uterus. Histopathology was consistent with cystic endometrial hyperplasia, suppurative metritis and pyometra. A uterine culture grew Escherichia coli . The dog ultimately made a full recovery.